2022
DOI: 10.3390/sym14071446
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Parameter Identification of a Real Manipulator Robot

Abstract: Given the widespread use of the Kalman filter in robotics, an increasing number of researchers devote themselves to its study and application. This work underscores the importance of this filter while analyzing the modifications made to the same to improve its performance and reduce its deficiencies in some fields and presenting some of its applications in robotics. The following methods are presented in this study: least squares (LS), Hopfield Neural Networks (HNN), Extended Kalman filter (EKF), and Unscented… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 35 publications
0
1
0
Order By: Relevance
“…This paper uses a 6R general industrial robot as an example to test the proposed method, as shown in Figure 1. Firstly, the robot's coordinate system is established based on the MD-H method [18]. In turn, the kinematic parameters of the robot are obtained, as shown in Table 2, where α i−1 denotes the link length of joint i − 1, i.e., the length of the common vertical line between joint axis i − 1 and joint axis I; a i−1 denotes the link twist angle, i.e., the angle between the two axes of axis i − 1 rotating to axis i around a i−1 ; θ i denotes the joint rotation angle of joint i, i.e., the angle between the two adjacent linkages rotating around the common axis; and d i denotes the link i offset, i.e., the distance along the common axis of two adjacent links.…”
Section: Robot Kinematic Modelingmentioning
confidence: 99%
See 2 more Smart Citations
“…This paper uses a 6R general industrial robot as an example to test the proposed method, as shown in Figure 1. Firstly, the robot's coordinate system is established based on the MD-H method [18]. In turn, the kinematic parameters of the robot are obtained, as shown in Table 2, where α i−1 denotes the link length of joint i − 1, i.e., the length of the common vertical line between joint axis i − 1 and joint axis I; a i−1 denotes the link twist angle, i.e., the angle between the two axes of axis i − 1 rotating to axis i around a i−1 ; θ i denotes the joint rotation angle of joint i, i.e., the angle between the two adjacent linkages rotating around the common axis; and d i denotes the link i offset, i.e., the distance along the common axis of two adjacent links.…”
Section: Robot Kinematic Modelingmentioning
confidence: 99%
“…This paper uses a 6R general industrial robot as an example to test the proposed method, as shown in Figure 1. Firstly, the robot's coordinate system is established based on the MD-H method [18]. In turn, the kinematic parameters of the robot are obtained, as shown in Table 2, where…”
Section: Robot Kinematic Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…SMC has two modes: reachability and sliding. Regarding other control methods, SMC offers advantages in the tracking of manipulator robot trajectories, specifically rapid response, good transient performance, a simple control law, and robustness in non-linear systems that vary over time and are subject to external disturbances and/or parameter uncertainty [91,92].…”
Section: Sliding Mode Controlmentioning
confidence: 99%
“…Knowing the dynamics can guide both the design and construction of robot systems, including the selection of their actuators and transmission components to initiate motion. Particularly, dynamic equations play an important role in real-time control applications, as they help determine the forces/torques necessary to generate the desired trajectories (position, velocity, and acceleration) [18].…”
Section: Introductionmentioning
confidence: 99%